Anticipatory feelings: Neural correlates and linguistic markers. (June 2020) - Stefanova, Elka; Dubljević, Olga; Herbert, Cornelia; Fairfield, Beth; Schroeter, Matthias L.; Stern, Emily R.; Urben, Sébastien; Derntl, Birgit; Wiebking, Christine; Brown, Carina; Drach -Zahavy, Anat; Kathrin Loeffler, Leonie Anne; et al.
Highlights: A new feeling construct related to anticipation of future events is introduced from a neurophysiological perspective. The insula; the ventromedial prefrontal cortex and the amygdala, play a key role in future oriented feelings. A novel meta-analysis on a platform for large-scale, automated synthesis of fMRI data on anticipatory feelings is reported. Adopting a neurolinguistics and a big data approach, illustrate how anticipatory feelings are expressed in English language. Abstract: This review introduces anticipatory feelings (AF) as a new construct related to the process of anticipation and prediction of future events. AF, defined as the state of awareness of physiological and neurocognitive changes that occur within an oganism in the form of a process of adapting to future events, are an important component of anticipation and expectancy. They encompass bodily-related interoceptive and affective components and are influenced by intrapersonal and dispositional factors, such as optimism, hope, pessimism, or worry. In the present review, we consider evidence from animal and human research, including neuroimaging studies, to characterize the brain structures and brain networks involved in AF. The majority of studies reviewed revealed three brain regions involved in future oriented feelings: 1) the insula; 2) the ventromedial prefrontal cortex (vmPFC); and 3) the amygdala. Moreover, these brain regions were confirmed by a meta-analysis, using a platform for large-scale, automated synthesis of fMRI data. Finally, by adopting a neurolinguistic and a big data approach, we illustrate how AF are expressed in language.